2010
DOI: 10.1074/jbc.c110.185777
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Suppresses Th17 Cytokine Production by Inducing C/EBP Homologous Protein (CHOP) Expression

Abstract: Vitamin D is an essential nutrient that regulates calcium and phosphate transport and bone mineralization (1). In recent years, however, vitamin D has been found to have a much broader range of actions, including regulation of cell differentiation, proliferation, and apoptosis (2). The role of vitamin D in immune system is complex and diverse. The systemic or locally produced active form of vitamin D, 1,25-dihydroxyvitamin D 3 (1,25D3), 3 can exercise its effects on several immune cells, including macrophages,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
132
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(145 citation statements)
references
References 23 publications
8
132
0
5
Order By: Relevance
“…We found no significant enhancing effects of 1,25-(OH) 2 D 3 on CD4 + Foxp3 + Treg cells in Wt or GKO mice, confirming and extending previous data in the EAE model (11,47). Those studies found very low Vdr gene expression in CD4 + Foxp3 + Treg cells, suggesting these cells may be relatively unresponsive to 1,25-(OH) 2 D 3 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We found no significant enhancing effects of 1,25-(OH) 2 D 3 on CD4 + Foxp3 + Treg cells in Wt or GKO mice, confirming and extending previous data in the EAE model (11,47). Those studies found very low Vdr gene expression in CD4 + Foxp3 + Treg cells, suggesting these cells may be relatively unresponsive to 1,25-(OH) 2 D 3 .…”
Section: Discussionsupporting
confidence: 80%
“…Vdr transcript abundance was very low in Foxp3-expressing regulatory T cells (Tregs) (11). Because Vdr low-expressing Treg cells are a minority (,1%) of the infiltrating cells and are fewer in GKO mice than Wt mice at EAE stage 3, and most infiltrating cells are Vdr high-expressing Th1 cells, Th17 cells, and macrophages (32,39,46,47), the reduced Vdr expression in GKO mice is unlikely to be explained by the composition of the cellular infiltrate.…”
Section: Vdr Expression Was Dramatically Lower In the Cns Of Gko Micementioning
confidence: 99%
“…86 Actually, the IL-17A-dependent response was found to occur in parallel with the Th1-dominant and unfavorable immune response during the atherogenic process. Treatment of T cells in vitro with 1a,25(OH) 2 D 3 suppressed the development of Th17 and inhibited IL-17 production via a posttranscriptional mechanism 87 ( Figure 1). 90 Moreover, 1a,25(OH) 2 D 3 acting as a natural endoplasmic reticulum stress reliever was found to induce an M1 antiatherogenic macrophage/monocyte phenotype over M2 (with increased cholesterol uptake and deposition) and to decrease mRNA expression of the monocyte adhesion molecules PSGL-1, β(1)-integrin, and β(2)-integrin, resulting in an increase of monocyte adhesion to activated endothelium.…”
Section: Effects Of Vitamin D On Immune Cellsmentioning
confidence: 99%
“…Diverse disorders such as asthma and autoimmune diseases associated with Westernized living are widely believed to result from insufficient levels of IL-10 and insufficient immune calibration essential for sustained systemic health [60]. Westernized diets are also low in vitamin D, a nutrient that normally works together with IL-10 to enforce immune tolerance and protect against inflammatory disorders [61][62][63] and some types of cancer [64].…”
Section: Cd25mentioning
confidence: 99%